Royals at war : the untold story of Harry and Meghan's shocking split with the House of Windsor - Howard, Dylan; Tillett, Andy; Mohammed, Arsalan (New York, NY : Skyhorse Publishing, 2020)
This expos?, takes readers inside Buckingham Palace to provide an account of the unfolding abdication of 2020.
The divisive duchess -- A commoner practice like none before -- Forced to flee -- "A bit of tension" -- "Deeply held differences" -- Unhappy birthday -- The $500,000 woman -- God bless the child -- Zooming around the world -- Going rogue -- A costly withdrawal -- The making of Meghan -- A tale of two commoners -- Carole meets her captain -- Poor little chap -- "I pushed her down the stairs" -- Charles and the sweet-charactered girl -- Wasting away -- The furious bride -- The heir and the spare -- Royal affairs -- Miserably ever after -- "You'll be king, I won't!" -- The death of Diana -- "A tidal wave of grief" -- Case closed -- Royal welcome for the other woman -- William weathers the storm -- The reign down in Africa -- "Wow, Kate's hot!" -- Better stand back -- There's something about Kate -- Waity Katie -- Learning to fly -- The split and the reunion -- Will and Kate get hitched -- The Diamond Jubilee -- Another pair of heirs -- The Prince's partners in crime -- Put back of the public eye -- Dirty Harry -- A star is born -- Meghan : steppin' out -- Intelligent hot messes -- Southern sojourn, hustle to Hollywood -- One-woman pity party -- "This is the one" -- The ring returned to sender -- When Harry met Meghan -- This is not a game -- "What Meghan wants, Meghan gets" -- Tears and tiaras -- The wedding walk that wasn't -- The power of love -- Windsors & losers.
NLJCols20082021
Keywords: Windsor, House of; Harry, -- Prince, Duke of Sussex, -- 1984-; Meghan, -- Duchess of Sussex, -- 1981-; Harry, -- Prince, Duke of Sussex, -- 1984-; Windsor, House of; Great Britain -- Kings and rulers -- Biography; Monarchy -- Great Britain -- History -- 21st century; Monarchy; Kings and rulers; Great Britain; 2000-2099; History; Biographies; Biographies